THE LIVED EXPERIENCE OF PATIENTS WITH PRE-DIALYSIS CHRONIC KIDNEY DISEASE: A QUALITATIVE STUDY - Tri Hapsari Retno Agustiyowati; Ratna Sitorus; Agung Waluyo; Besral Besral (Belitung Nursing Journal, 2018)
Background: Chronic kidney disease is identified as kidney damage for more than three months with glomerulus filtration rate less than 60ml / min / 1.73 m2. Objective: This study aims to explore the experience of life of patients with pre-dialysis chronic kidney disease used Roy’s adaptation model. Methods: This study was a qualitative study using descriptive phenomenology approach in the General Hospital of Cibabat Cimahi West Java, Indonesia. Data were obtained with depth interviews involved eight participants with pre-dialysis chronic kidney disease consisting of two men and six women, aged ranged from 35 to 65 years. The years living with chronic kidney disease ranged from 1 to 2 years. Data were analyzed using Colaizzi’s methods. Results: We found nine themes, namely: physical stimulus, psychic stimulus, socio-economic stimulus, physical coping mechanisms to control the situation, a coping mechanism to maintain health function, selecting behavioral adaptation physiology, selecting a behavior adaptation of the self-concept, selecting adaptation behaviors role function, and selecting behavioral adaptation interdependence. Conclusion: It can be concluded that the experience of patients with pre-dialysis chronic kidney disease complained physical, psychological, social, economic, and spiritual problems. Therefore, health care professionals need to design an intervention to improve patients’ coping mechanism to maintain kidney function, and adapt to diet for foods and drinks, activity patterns and roles according to their conditions, which also elaborate the function of family support.